2016
DOI: 10.7175/fe.v17i1.1219
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the treatment cost of HIV/AIDS in Turkey

Abstract: OBJECTIVE: Infection with the human immunodeficiency virus (HIV), the causative agent of acquired immune deficiency syndrome (AIDS), is a major global health problem. Patients with HIV can live normal lives with today’s new treatment options. As the treatment is generally successful, the life expectancy of patients infected with HIV is rising. As a result, the economic burden of HIV treatment on health systems is set to increase. According to the Ministry of Health, there were more than 6000 HIV-positive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In addition, we have shown that the findings of our GLM indicate that these socioeconomic parameters and CD4 cell count are the factors significantly related to the healthcare costs of patients. A number of studies show that HAART reduces the average number of annual hospitalisations, and hence results in considerable cost savings [49][50][51]. But the literature lacks the information regarding PLHIV already on HAART and how other factors, such as socioeconomic, are affecting the healthcare costs of PLHIV.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have shown that the findings of our GLM indicate that these socioeconomic parameters and CD4 cell count are the factors significantly related to the healthcare costs of patients. A number of studies show that HAART reduces the average number of annual hospitalisations, and hence results in considerable cost savings [49][50][51]. But the literature lacks the information regarding PLHIV already on HAART and how other factors, such as socioeconomic, are affecting the healthcare costs of PLHIV.…”
Section: Discussionmentioning
confidence: 99%
“…HIV can be transmitted through direct contact with contaminated blood products, such as syringes or needles, contaminated transfusion, unprotected sexual intercourse, and breastfeeding or as a vertical transmission during birth [7]. However, not all HIV cases necessarily result in AIDS infection.…”
Section: Introductionmentioning
confidence: 99%